Learning Leadership in the Implementation of Independent Learning in Effective Schools - Mas, Sitti Roskina; Zulystiawati, Zulystiawati (Jurnal Pedagogi dan Pembelajaran, 2022)
The role of leadership has not been maximized by the majority of school principals, especially in Indonesia. This study aims to analyze the principal's learning leadership role in the implementation of independent learning. This study used a qualitative approach with a case study design at one madrasah school. Interviews, observations, and documentation studies were used to collect the data. All data obtained were analyzed with theme analysis approach, including data reduction, presentation, and verification procedures. Test the validity of the data using the credibility of the data and confirmability of the data. The results showed that the principal has focused on learning leadership well and effectively. Efforts that the principal has made as the highest leader in the school and as a learning leader are actively and continuously accompanying, guiding, facilitating, and motivating teachers to organize quality learning and innovative learning through good and structured academic guidance, deepening the interests of the academic community planned and programmed, as well as intensive religious/pesantren development as a characteristic of Islamic boarding schools to produce superior graduates, have character, and are competitive following the school's vision and mission. Furthermore, this study also shows that selecting appropriate and effective leadership approaches and strategies in each madrasa program will result in maximum student academic achievement. Principals' current and updated approach to learning leadership can create effective schools by implementing independent learning programs.